Impact of multiple drug-resistant Gram-negative bacterial bacteraemia on infected pancreatic necrosis patients - Wu, Di; Jia, Yan; Cai, Wenhao; Huang, Yilin; Kattakayam, Arjun; Latawiec, Diane; Sutton, Robert; Peng, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Multiple drug-resistant Gram-negative bacterial (MDR-GNB) bacteraemia poses a serious threat to patients in hospital. Infected pancreatic necrosis (IPN) patients are a vulnerable population to infectious complications during hospitalization. This study aims to evaluate the impact of MDR Gram-negative bacteraemia on IPN patients. Methods A case–control study was performed with data collected from 1 January 2016 to 1 July 2022 in a Chinese tertiary teaching hospital. Clinical data of the IPN patients with MDR-GNB bacteraemia were analyzed and compared to those of a matched control group without MDR-GNB bacteraemia (case–control ratio of 1:2). Comparisons were performed between with/without MDR-GNB bacteraemia and different severities of acute pancreatitis (AP). Independent predictors of overall mortality were identified via univariate and multivariate binary logistic regression analyses. Results MDR-GNB bacteraemia was related to a higher mortality rate (62.5% vs. 8.3%, p < 0.001). Severe AP combined with MDR-GNB bacteraemia further increased mortality up to 81.3% (p = 0.025). MDR-GNB bacteraemia (odds ratio (OR) = 8.976, 95% confidence interval (CI) = 1.805 –44.620, p = 0.007) and severe AP (OR = 9.414, 95% CI = 1.742 –50.873, p = 0.009) were independent predictors of overall mortality. MDR- Klebsiella pneumoniae was the most common causative pathogen. Conclusion A higher mortality rate in IPN patients was related to MDR-GNB bacteraemia and further increased in severe AP patients combined with MDR-GNB bacteraemia.